Pemantauan gizi dengan SMS reminder efektif meningkatkan kepatuhan diet pasien hemodialisis - Fery Lusviana Widiany; Yuni Afriani (Jurnal Gizi Klinik Indonesia, 2019)
Nutritional monitoring with SMS reminder is effective to increase the dietary compliance of hemodialysis patientsBackground: Patients with routine hemodialysis are at risk of malnutrition, inadequate intake of protein, hypoalbuminemia, gastrointestinal disorders. One of the factors affecting dietary compliance is knowledge so that the education and nutrition monitoring on an ongoing basis is necessary. Objective: To determine the effectiveness of nutrition monitoring with SMS reminders on dietary compliance of hemodialysis patients.Methods: This was a quasi-experimental study that involved 30 regular hemodialysis patients, divided into two groups. The inclusion criteria were aged >18 years, willing to become respondent and following the procedure, have a handphone, able to read and write. Patients with anasarca edema and complications of malignancy disease were excluded. The independent variable is nutritional monitoring with SMS reminders, while the dependent variable is dietary compliance. Data were statistically analyzed using the Chi-Square test and multiple logistic regression test. Results: Statistical analysis showed that nutritional monitoring with SMS reminder effectively influences the compliance on the consumption of energy (p=0.011, RR=2.750), fluid (p=0.014, RR=2.000), and potassium (p=0.011, RR=2.750). The compliance on the consumption of fluid is the most dominant factor affected by nutrition monitoring with SMS reminders given (B=3.676, p=0.02).Conclusions: Nutritional monitoring with SMS reminders is effective to increase the dietary compliance of hemodialysis patients.